Meningkatkan Literasi Melalui Bahan Ajar Tematik Saintifik Berbasis Kearifan Lokal - Nuhyal Ulia; Yulina Ismiyanti; Leli Nisfi Setiana (University of Islam Malang, 2019)
The literacy movement is being carried out by the government nationally in various circles ranging from families, schools and communities. It is also entitled to be felt by all people including street children. For street children literacy culture also needs to be grown because their literacy is still low. This effort was carried out by increasing literacy in